Beauty Beyond the Golden Ratio: A Study of Perception Regarding Facial Proportions and Symmetry in the Turkish Population - Özlem Özgür; Leo Can Mazlum; Billur Sezgin Kızılok (Gazi Medical Journal)
Objective: The authors examined the effect of previously described facial proportions and facial asymmetry on the perception of beauty and attractiveness. The optimal values of four different facial ratios and the optimal degree of asymmetry were examined. Methods: In this study, 10 faces were adjusted to reference values and -5%, -2.5%, +2.5%, and +5% deformations were created. Participants were asked to select via online survey the most and least attractive face between 5 photographs of the same person with different facial ratio values. Finally, split-face imaging was used to generate right and left-symmetrical images. These images along with the original images were questioned to determine the most and least attractive. Results: The most attractive face was closer to the reference ratio, whereas the least attractive face was most distant from the reference. Both left and right symmetrical faces were considered less attractive than natural asymmetrical faces. Conclusion: Standardized “golden” ratios are effective reference points for the perception of facial attractiveness although deviation from these proportions does not always imply that a face will not be perceived as attractive, as some degree of asymmetry also contributes to facial attractiveness and beauty.